Infraorbital ethmoid (Haller) cells: a cone-beam computed tomographic study - DUMLU, ASIM; NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (SPRINGER, 2014)
Infraorbital ethmoid (Haller) cells are extensions of the anterior ethmoid sinus into the floor of the orbit and superior aspect of the maxillary sinus. The aim of this retrospective study was to evaluate the frequency, volume, and surface area of infraorbital ethmoid cells on cone-beam computed tomography (CBCT). In this retrospective study, 150 CBCT evaluations were determined for infraorbital ethmoid cells. One CBCT examination was carried out for each of the patients and interpreted for the presence of infraorbital ethmoid cells. Volumetric measurements were performed using CBCT scans. All of the CBCT scans were assessed and analyzed using MIMICS 14.0 software. In the 150 CBCT evaluations, 65 (43.3 %) were noted as having infraorbital ethmoid cells. In these patients, 47 (31.3 %) were unilateral and 18 (12 %) bilateral. The majority of the cells were round in shape. The frequency of unilocular infraorbital ethmoid cells occurring unilaterally was highly significant. There were no significant differences in the volume and surface area of right and left infraorbital ethmoid cells between males and females. Infraorbital ethmoid cells were well demonstrated and the volume and surface area of infraorbital ethmoid cell could be measured on CBCT scans. These cells may provide useful differential diagnoses for patients suffering from orofacial pain of sinus origin.
Keywords: Cone-beam computed tomography; Infraorbital ethmoid cells; Volume; Surface area; ANATOMIC VARIATIONS; PARANASAL SINUSES; CT; PNEUMATIZATION; SINONASAL; NASAL